Household Food Insecurity among Small-scale Fishermen in Tambak Lorok Semarang - Subekti, Slamet (Journal of Maritime Studies and National Integration, 2022)
This paper discusses food insecurity which reflects the absence of sufficient food availability in a family to be able to live a healthy, active, and productive life in a sustainable manner. The condition of household food insecurity can be identified using a method based on an experience-based measurement scale. In connection with the existence of traditional fishermen in Tambak Lorok Semarang, it is deemed necessary to conduct research on the scale of measuring household food insecurity. The purpose of this research is to determine the level of food insecurity in traditional fishing households in Tambak Lorok Semarang. The results of this study concluded that the food insecurity of Tambak Lorok fishermen's households was at a moderate level close to severe.